Reward and Punishment System at Alfamart Said Sudirman - Setyawati, Irma; Nugraha, Rizki Nurul; Rambe, Delila (Westscience Press, 2024)
This research is entitled Reward and Punishment System at Alfamart Said Sudirman. This research was conducted to examine the implementation of reward and punishment systems at Alfamart as one of the main players in the minimarket industry in Indonesia. The location of this research was conducted on Jl. Jenderal Sudirman, Sahid City Complex, Karet Tengsin, Tanah Abang, Central Jakarta, DKI Jakarta. With a focus on the effectiveness of these strategies in motivating employees and managing rule violations, this study aims to provide an in-depth picture of Alfamart's efforts in maintaining employee performance amid fierce competition. The research method used is a qualitative approach with a descriptive type of research, involving observation and interviews with HRD Alfamart to obtain the information needed to compile research. The results showed that Alfamart implemented a reward strategy in the form of rewards for employee achievements and punishment in response to violations of rules. The conclusions and suggestions provided emphasize the importance of communication, transparency, and periodic evaluation in the implementation of both strategies.